2022
DOI: 10.2478/jeb-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remittances on Economic Growth: Empirical Evidence from South-East European Countries

Abstract: South-East European (SEE) countries are experiencing high emigration, resulting in a significant increase in remittance inflows, exceeding FDI flows. Today the most important challenge facing SEE countries is how to grow at a higher speed to achieve faster economic convergence with the EU. The objective of the paper is to empirically examine the relevance of remittances as a factor of economic growth, using quarterly balanced panel data set of six SEE countries: Albania, Bosnia and Herzegovina, Croatia, Monten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…For example, Goschin (2014) identified that in CEE countries remittances have a positive effect on both GDP and GDP growth rate. A similar positive result on economic growth was found in the recent paper of Bucevska (2022), which conducted a panel data analysis on 6 SEE countries for 2008q1-2020q2. In addition, the positive effect has also been identified in larger samples or time spans (see, e.g., Batu, 2017;Simionescu and Dumitrescu, 2017).…”
supporting
confidence: 82%
“…For example, Goschin (2014) identified that in CEE countries remittances have a positive effect on both GDP and GDP growth rate. A similar positive result on economic growth was found in the recent paper of Bucevska (2022), which conducted a panel data analysis on 6 SEE countries for 2008q1-2020q2. In addition, the positive effect has also been identified in larger samples or time spans (see, e.g., Batu, 2017;Simionescu and Dumitrescu, 2017).…”
supporting
confidence: 82%
“…The authors used the panel analysis to show that workers' remittances have a significant impact on economic growth in the observed countries. Besides the mentioned research efforts, the positive impact of remittances on economic growth has been confirmed in Cartinescu et al (2009), Bucevska (2022), Faini (2007), Ziesemer (2006), Chaimi et al (2005. Rao and Hassan (2009) point to a somewhat smaller impact of remittances on economic growth.…”
Section: Literature Reviewmentioning
confidence: 80%
“…The link between remittances and economic growth continues to be the subject of a debate that lacks a definitive consensus. On the one hand, several studies indicate that remittances contribute to economic growth through their positive impacts on consumption, investment, and savings (see, for example, Meyer and Shera 2017;Golder et al 2023;Villanthenkodath and Ansari 2023;Klaiqi et al 2023;Khan 2023b;Bucevska 2022;Pal et al 2022;Dutta and Saikia 2022). On the other hand, there is research suggesting that remittances can have a positive effect in the short term but that a permanent transfer of these resources does not necessarily translate into sustainable output growth (Batu 2017;Qutb 2022).…”
Section: Linking Remittances Economic Growth and Energy Povertymentioning
confidence: 99%